Spatial Distribution of Soil Nitrogen, Phosphorus and Potassium Contents and Stocks in Humid Subtropical North-Eastern India - S. Bandyopadhyay, S. Mukhopadhyay, K.d. Sah, D.c. Nayak, S.k. Singh2 and S.k. Ray, S.k. Reza*, P. Ray, S. Ramachandran (Journal of the Indian Society of Soil Science, 2019)
Soil nitrogen (N), phosphorus (P) and potassium (K) are important macronutrients for crop production and productivity. Assessment of spatial distribution and stock of N, P and K in soil are the need of the hour for judicious nutrient management through precision agriculture. An attempt was made to prepare the spatial distribution map of available macronutrients in soil using geostatistical techniques. In total 150 geo-referenced surface soil samples (0-25 cm depth) were collected at 1 km Ã— 1 km grid interval in three major land use systems viz., crop, plantation and agroforestry (like Mangifera indica, Syzigium cumini, Shorea robusta, Tectona grandis, Acacia auriculiformis and Bambusa sp.) from Bishalgarh block, Sepahijala district, Tripura of North-eastern India. Data indicates that soil bulk density (BD), and available N, P and K varied from 1.10 to 1.82 g cm-3, 0.01 to 0.29 g kg-1, 0.001 to 0.02 g kg-1 and 0.02 to 0.24 g kg-1, respectively. Stock of N, P and K in these soils varied from 0.33 to 8.71, 0.02 to 0.69 and 0.72 to 8.52 Mg ha-1, respectively. Perusal of dataset under different land use systems revealed that stock of available N, P and K in surface soil followed the order of plantation land > agroforestry land > cropland. Geostatistical analyses indicated that spherical model was best fitted for N and P content in soil, while exponential model was best fitted for K content. Similarly, stocks of N, P and K in soil could be best fitted by exponential model. The nugget/sill ratio indicates a strong dependence for N (5%), a weak spatial dependence for K stock (81%) and moderate spatial dependence for all other soil variables (51-69%). The spatial distribution maps of macronutrients in soil exhibited differential distribution pattern indicate the need of differential soil application rates in respect of N, P and K. Such study is of practical significance in managing soil resources through judicious application of fertilizers under precision agriculture.